PELESTARIAN KESENIAN TRADISIONAL MASYARAKAT BADUY DI ERA MODERN - Samsudin; Sapriya; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Baduy people are known as one of the indigenous groups in Indonesia that uphold their traditions and culture, including in the arts. The arts of the Baduy people are not only a means of aesthetic expression, but also reflect philosophical, spiritual values, and local wisdom that are passed down from generation to generation. This article aims to examine various forms of traditional arts of the Baduy people, such as weaving, weaving, and ritual arts, and the meanings contained therein. In the context of modernization and globalization, Baduy arts face major challenges, including in terms of preservation and commercialization. Through a qualitative approach with literature study methods and field observations, this study found that the arts of the Baduy people not only function as a cultural identity, but also as a medium to maintain harmonious relations between humans, nature, and the Creator. In addition, the results of the study show that the Baduy people continue to strive to maintain the authenticity of their arts despite facing changing times. This article recommends strengthening cultural preservation strategies through local education and the development of sustainable culture-based tourism. Thus, the traditional arts of the Baduy people can continue to live and develop, while providing inspiration for modern society.